1997
DOI: 10.1046/j.1365-2141.1997.3263141.x
|View full text |Cite
|
Sign up to set email alerts
|

Atypical lymphocyte morphology: an adverse prognostic factor for disease progression in stage A CLL independent of trisomy 12

Abstract: Summary.We studied 270 patients with Binet stage A chronic lymphocytic leukaemia looking for adverse prognostic factors. In a multivariate analysis the following features were found to be risk factors for disease progression: atypical lymphocyte morphology (defined as either > 10% prolymphocytes or > 15% lymphocytes with cleaved nuclei or lymphoplasmacytoid cells); more than two karyotypic abnormalities; lymphocyte count > 30 × 10 9

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
2
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 31 publications
2
35
2
4
Order By: Relevance
“…In this cohort of strictly classified CLL patients the rates of spontaneous apoptosis and response to fludarabine and cladribine showed wide variation and no significant difference was apparent between patients with typical or atypical CLL (Table 2). Atypical CLL is clinically more aggressive than typical CLL, 17 however, the results presented here imply that atypical CLL lymphocytes are not more resistant to the in vitro induction of apoptosis. When the effect of prior treatment was examined, 13 patients who had completed therapy more that 6 months before assessment (but with significant disease present) were compared with 35 previously untreated patients (one patient receiving treatment immediately prior to the assay was excluded from analyses); analyses showed no statistically significant difference (Mann-Whitney U test) between the two groups for either spontaneous or drug-induced response (Table 3A).…”
Section: Drug Sensitivity Assaycontrasting
confidence: 53%
See 1 more Smart Citation
“…In this cohort of strictly classified CLL patients the rates of spontaneous apoptosis and response to fludarabine and cladribine showed wide variation and no significant difference was apparent between patients with typical or atypical CLL (Table 2). Atypical CLL is clinically more aggressive than typical CLL, 17 however, the results presented here imply that atypical CLL lymphocytes are not more resistant to the in vitro induction of apoptosis. When the effect of prior treatment was examined, 13 patients who had completed therapy more that 6 months before assessment (but with significant disease present) were compared with 35 previously untreated patients (one patient receiving treatment immediately prior to the assay was excluded from analyses); analyses showed no statistically significant difference (Mann-Whitney U test) between the two groups for either spontaneous or drug-induced response (Table 3A).…”
Section: Drug Sensitivity Assaycontrasting
confidence: 53%
“…In this report, strict morphological and immunophenotypic criteria have been used to define the patient population and inclusion has been restricted to CLL only. 16 A recent report suggested that atypical CLL was more likely to progress clinically than typical CLL, 17 implying that some fundamental difference exists between these two subtypes of disease. The present belief that CLL arises through a defect in the apoptotic pathway raises the question as to whether typical and atypical CLL show similar apoptotic responses, and led to the further classification of patients in this report as typical and atypical CLL.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Early in the 1990s, conventional cytogenetic analysis (CCA) demonstrated that approximately 50% of CLL cases may show clonal aberrations and that specific cytogenetic patterns have independent prognostic significance. 6 A complex karyotype was associated with an inferior outcome and patients with trisomy 12 in their karyotype were shown to survive less than patients with 13qÀ or with normal karyotype.…”
Section: Introductionmentioning
confidence: 99%
“…7 Later on, fluorescence in situ hybridization (FISH) techniques demonstrated that up to 80% of the cases may carry a chromosomal defect in interphase cells, 8 giving the opportunity to better analyze the correlations of cytogenetic lesions and clinicobiological features. Convincing evidence was provided that: (a) 13q deletion occurring as an isolated chromosome lesion is associated with typical morphology and a benign clinical course; 4,5 (b) patients with trisomy 12 usually display an excess of large lymphocytes identifying the CLL mixed-cell-type variant of the FAB classification; 9,10 (c) 11q22-23 and 17p13 deletion may identify specific clinicopathological subsets of CLL having an inferior outcome. [11][12][13] A hierarchical cytogenetic classification was finally defined as having a strong correlation with the clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…However, they do not distinguish which patients in early stages of the disease will progress. Other prognostic parameters, e.g., short lymphocyte doubling time and/or diffuse bone marrow infiltration are known risk factors for progressive disease in early-stage CLL [2,3]. Although patients lacking these features have a low risk for disease progression, 10-15% of such cases will still progress within 5 years of diagnosis, emphasizing the need for additional prognostic factors in early CLL [3,4].…”
Section: Introductionmentioning
confidence: 99%